2021
DOI: 10.1097/opx.0000000000001668
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanical Changes Caused by Acute Elevation of IOP in Eyes with and without Glaucoma

Abstract: SIGNIFICANCE Although corneal biomechanical parameters are well linked with glaucoma, their clinical utility has not yet been fully elucidated. This study was designed to provide unique evidence about the dynamic nature of corneal biomechanical parameters and their potential prognostic ability for glaucoma. PURPOSE This study aimed to evaluate the effect of acute intraocular pressure (IOP) elevation on corneal hysteresis (CH) and corneal resistance fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Earlier studies have shown an inverse relationship between corneal hysteresis and IOP, i.e., as IOP decreases, corneal hysteresis increases [47,48]. Katiyar et al [49 ▪ ] induced a decrease in corneal hysteresis by 21% by doubling IOP from 15 to 30 mmHg in human eyes using a ophthalmodynamometer. Corneal hysteresis has also been shown to significantly increase after trabeculectomy and tube shunt surgeries [50], especially when IOP was reduced by more than 10 mmHg [51].…”
Section: Limitations and Special Situationsmentioning
confidence: 99%
“…Earlier studies have shown an inverse relationship between corneal hysteresis and IOP, i.e., as IOP decreases, corneal hysteresis increases [47,48]. Katiyar et al [49 ▪ ] induced a decrease in corneal hysteresis by 21% by doubling IOP from 15 to 30 mmHg in human eyes using a ophthalmodynamometer. Corneal hysteresis has also been shown to significantly increase after trabeculectomy and tube shunt surgeries [50], especially when IOP was reduced by more than 10 mmHg [51].…”
Section: Limitations and Special Situationsmentioning
confidence: 99%
“…However, the prognostic value of these corneal measurements remains an open question. Therefore, recent studies also focus on associating measurable corneal properties to supplement more conventional outcome measures and hence better quantify glaucoma risk [64], and the impact of these parameters for clinical use is a work in progress.…”
Section: Key Pointsmentioning
confidence: 99%